IMPROVING ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR SUPPORTING WOMEN'S ENTREPRENEURSHIP IN THE SERVICE SECTOR - Аbdurаimоvа Nilufаr Xusenоvnа (The Conference Hub, 2025)
This article focuses on the enormous potential of women's entrepreneurship in the service sector. The important and significant aspects of women's entrepreneurship are studied in depth.
Keywords: training, financial assistance, digital tools, support, learning, international grants, digital platforms.